Analysis of off-label drug use and its influencing factors in pediatric patients undergoing otolaryngology, head, and neck surgery - Ji, Zichao; Wang, Xin; Wang, Jiawei (Frontiers in Pharmacology, 2025)
BackgroundTo date, there are limited data regarding off-label drug use in pediatric patients undergoing otolaryngology, head, and neck surgery. This study aimed to investigate the prevalence and patterns of off-label drug use among outpatients under 18 years of age in the Otolaryngology, Head, and Neck Surgery department, and to analyze the factors influencing such usage.MethodsA retrospective collection of data was conducted based on outpatient prescriptions for patients under 18 years of age who were visited from November 2023 to October 2024. Clinical pharmacists collected and analyzed off-label drug use. Univariate and multivariate logistic regression were employed to analyze the factors associated with off-label drug use.ResultsIn total, 22,487 prescriptions were included, of which 2,269 were off-label, resulting in an incidence rate of off-label drug use of 10.09%. Among 2,269 off-label prescriptions, the most common type was off-label population use (2,090 instances), accounting for 92.11%. The 2,269 off-label prescriptions encompassed 2,359 records of off-label drug use. Limonene and Pinene enteric capsules had the highest frequency of off-label use, with 1,523 records, representing 64.56% of all off-label uses. Multivariate logistic regression analysis showed that patients’ age (OR = 1.341, 95% CI: 1.324 ∼ 1.359, p = 0.000), number of prescribed drugs (OR = 1.597, 95% CI: 1.528 ∼ 1.671, P < 0.001), and physician title were the factors associated with off-label drug use. Attending physicians (OR = 0.555, 95%CI: 0.458 ∼ 0.673, p < 0.001), deputy chief physicians (OR = 0.770, 95%CI: 0.637 ∼ 0.930, p = 0.007), and chief physicians (OR = 0.419, 95%CI: 0.347 ∼ 0.507, p < 0.001) were less likely to have off-label drug use compared to resident physicians.ConclusionThese findings indicate that pediatric patients who are older and receive a greater variety of medications are more likely to use drugs off-label. In addition, resident physicians exhibit a higher susceptibility for off-label drug use compared to attending physicians, deputy chief physicians, and chief physicians.